Polykinematic foreland basins initiated during orthogonal convergence and terminated by orogen-oblique strike-slip faulting: An example from the northeastern Variscan belt - Tomek, Filip; Vacek, František; Žák, Jiří; Petronis, Michael S.; Verner, Kryštof; Foucher, Marine S. (Tectonophysics, 2019)
An extensive early Carboniferous foreland basin (the Moravosilesian Culm Basin, MSCB) delineates the northeastern margin of the Bohemian Massif (Variscan orogenic belt). The basin overlays a complex suture between the outer Brunovistulia microplate, forming a promontory previously accreted to Laurussia, and inner Gondwana-derived units that form the remainder of the Bohemian Massif. Our structural, paleomagnetic and magnetic anisotropy data from the eastern portion of the MSCB indicate that its depositional architecture, internal fabric, and deformation by folding and faulting record a major switch from orthogonal convergence to orogen-oblique strike-slip shearing. First, the Brunovistulia microcontinent was subducted frontally towards W during ~346–335 Ma, followed by a shift of the subduction vector towards ~SSW at around 335–330 Ma. From ~330 Ma onwards, the underthrusting had ceased and the ~WNW–ESE dextral Elbe shear zone, related to the westward movement of Gondwana with respect to Laurussia, controlled deformation of this region. Displacement of the northerly Eastern Sudetes ‘block’ towards ~ESE produced regional ~WNW–ESE pure-shear shortening against the Brunovistulia indentor and resulted in an overall doubly-vergent structure of the MSCB. Simultaneously, the southerly Moldanubian unit was translated towards ~WNW, away from the Brunovistulian microplate, and likely contributed to an extensional regime related to orogenic collapse progressing outward from the internal domains of the Bohemian Massif. On a larger scale, we suggest that the MSCB is an illustrative example of a polykinematic foreland basin, where deposition, syn- to post-sedimentary deformation, and thus geodynamic processes changed significantly during basin evolution, starting off with microplate impingement into a continental margin reentrant and terminated by strike-slip shearing. Our data also do not support previous models for the tectonic development of the northeastern termination of the Variscan Belt, which suggested either a large-magnitude, vertical-axis oroclinal rotation of the foreland or its translation along an orogen-perpendicular strike-slip fault. •Structural, magnetic anisotropy and paleomagnetic study of a foreland basin•Late-orogenic Moravosilesian Culm Basin, northeastern Variscan belt•The deformational architecture developed in two stages•Basin records switch from frontal convergence to dextral strike-slip shearing•Shearing driven by westward movement of Gondwana with respect to Laurussia